Mean reversions in major developed stock markets: Recent evidence from unit root, spectral and abnormal return studies - James Nguyen; Wei-Xuan Li; Clara Chia Sheng Chen (Journal of Risk and Financial Management, 2022)
We revisited the issue of return predictability in three major developed markets (USA, UK and Japan) using a unique dataset from the Wharton Research Data Services database and a comprehensive set of traditional and recent statistical methods. We specifically employed a variety of traditional linear and nonlinear tests, latest multiple-break unit root tests and spectral analysis to test the efficient market hypothesis. Our results show that these stock markets generally are inefficient. We further explored whether the departure from market efficiency can be used to generate profitable trades and found that abnormal returns exist in all three markets. We found evidence of abnormal returns associated with the break dates identified in the models which are correlated with major historical events around the world. Our findings have important implications for investors and policymakers.
Keywords: 650; abnormal returns; efficient market hypothesis; spectral analysis; unit root